PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 003 SUNGAI MANASIB KECAMATAN BANGKO PUSAKO - Miftahurahmah Miftahurahmah; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of this research was students’ outcome for math lesson for students grade IV with average 63,39. While minimal criteria completeness (KKM) for math lesson was 70. From 28 students, only 12 students passed the KKM. This research was classroom action research. The aim of this research was to increase students’ achievement math lesson for students grade IV SDN 003 Sungai Manasib Kecamatan Bangko Pusako by using Realistic Math Learning Approach. The data shown that students achievement in math lesson had increase from average basic data 63,39 increase to 10,53 points become 73,92 in the first cycle. In the second cycle increased 16,79 points become 90,17 from first cycle. In the firts cycle, 22 students was complete and 6 students was not complete. Classical completeness first cycle was 78,75%. In the second cycle, all of students were complete. Classical completenese second cycle was 100%. Teacher’s activities during learning process also rise. In the first cycle at the first meeting teacher’s activity was 71,15% good category and increased 7,69% at the second meeting as 78,84% good category. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increased as 90,38% very good category and in the second meeting it increased as 5,77% so the percentage became 96,,15% very good category. At the firts cycle in the firts meeting, the percentage of students’ activities was 65,38% good category and the second meeting it increased as 11,54% so became 76,92% good category. At the second cycle in the firts meeting it increased to 88,46% very good category. At the second meeting the percentage of students activities increased as 3,84% became 92,30% very good category. From the result of the research above shown that the implementation Realistic Math Learning approach could increase learning math outcome for students’ grade IV SDN 003 Sungai Manasib Kecamatan Bangko Pusako.Keywords : Implementation Realistic Math Learning Approach, Learning Outcome